ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN PT XYZ DI JAKARTA - Rania (2022)
Job satisfaction is a feeling that is owned by employees whether they feel happy or unhappy with their work. The research method used is qualitative research with the aim of obtaining information and analyzing work satisfaction related to the construction work of PT XYZ employees in Jakarta. Data collection techniques used are interviews, observation, and documentation. The interviews used were semi-structured interviews with 7 people as participants. The data validation method used is the triangulation technique. Then the data were analyzed using data reduction, data presentation and drawing conclusions. The results that can be concluded from this study are that there are 5 indicators that influence employee job satisfaction in the Construction Section of PT XYZ, namely satisfaction with salary, satisfaction with colleagues, satisfaction with the work itself, satisfaction with supervision, promotion opportunities. Employees in the Construction Section job satisfaction is still relatively low because there are 3 indicators that become dissatisfaction factors, namely salary satisfaction, satisfaction with the job itself, promotion opportunities. While the indicators of satisfaction with co-workers and satisfaction with supervision have been able to meet the job satisfaction of employees in the Construction Section of PT XYZ.